OPTIMIZING REHABILITATION AS A PUNISHMENT FOR INDONESIAN NATIONAL ARMY SOLDIERS WHO ABUSE NARCOTICS (Lex localis - Journal of Local Self-Government, 2025)
Narcotics abuse crimes committed by the Indonesian National Army (TNI) personnel not only affect the individual offenders but also disrupt the integrity of the TNI institution, harm the government and society, and threaten national security stability. Therefore, the criminal justice system in Indonesia and the military disciplinary system impose strict sanctions on service members involved, mainly to maintain military discipline and integrity. This study analyses various narcotics abuse cases involving TNI personnel, examining the imposition of criminal sanctions by the Military Court, with a focus on the reasons behind judicial decisions that do not always include medical and social rehabilitation, aiming to propose the development of a more effective rehabilitation regulation to achieve comprehensive and fair penal objectives. This research employs a descriptive approach with a normative legal research method through literature study, utilizing primary, secondary, and tertiary legal materials, applying a statute approach and case approach to analyze qualitative data in a systematic and accountable manner to solve the research problem. The study finds two different approaches in Military Court judgments: one combines criminal penalties, such as imprisonment and dismissal, with an order for medical and social rehabilitation, while another emphasizes legal certainty without including rehabilitation. This difference reflects the judges' orientation, between focusing on rehabilitation for qualifying victims of narcotics abuse, and prioritizing rigid military discipline enforcement. Therefore, a revision of the rehabilitation regulations through the revision of SEMA and joint regulations is necessary to ensure consistent implementation of rehabilitation rulings in the military justice system with a double-track system approach, to maximize justice, prevent recidivism, and achieve optimal social recovery.